Open Questions on Gestational Diabetes Mellitus in Twin Pregnancies - Savoia, Fabiana; Muscettola, Giulia; Iliodromiti, Stamatina; Greco, Elena (Current Diabetes Reviews, 2023)
Background: The concurrent, recent increase in prevalence of Gestational Diabetes Mellitus (GDM) and twin pregnancy, in combination with the shared risk factors, has led to speculation that multiples are a risk factor for GDM and, GDM may contribute to twin complications. Twin pregnancies have different physiology and greater obstetric risks compared to singletons, including prematurity and growth restriction. However, in twins methods of GDM screening, thresholds for diagnosis and treatment, as well as glycaemic control targets, have been predominantly extrapolated from singletons. Studies investigating the impact of GDM on pregnancy outcomes in twin pregnancies are conflicting. Objective: To provide a comprehensive, critical overview of evidence on GDM in twin pregnancies with an emphasis on prevalence, methods of screening, thresholds for diagnosis, risk of pregnancy complications and the impact of treatment on perinatal outcomes. Methods: Review of retrospective and prospective cohort, case-control, and case-series studies on twin pregnancies with GDM published between 1980 and 2021. Results: Glucose tolerance in twin pregnancies is poorly studied. Specific guidance for screening, diagnosis, and treatment of GDM in twins is lacking. Studies evaluating pregnancy outcomes in twins with GDM are few and heterogeneous. The absolute risk of maternal complications is greater in twins with GDM compared to singletons; conversely, differences in risks between twins with and without GDM may be due to maternal confounders rather than to GDM. Most studies agree on a positive effect of GDM on neonatal outcomes in twins, likely mediated by the hyperglycaemia improving fetal growth. The impact of lifestyle-measures versus medical management on pregnancy outcomes in twins with GDM is unknown. Conclusion: Larger longitudinal studies evaluating glucose tolerance, pregnancy outcomes and the impact of treatment both in mono and di-chorionic twins with GDM are warranted to gain further insight into the pathophysiology of this condition and guide optimal management.
Keywords: twins